“Be the Auntie Rez Kids in Palestine Need Right Now”: Diné Civics and Solidarity for Palestine - Stanley, Jay; Sabzalian, Leilani (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2026)
Indigenous peoples throughout the world have long been subject to settler colonial violence and elimination. This ongoing legacy of settler colonialism and struggle for Indigenous self-determination provides a felt experience that connects many Indigenous people to Palestinians fighting settler colonial oppression and occupation in their homelands. In this article, we highlight examples of Indigenous solidarity with/for Palestinians and look closely at the advocacy of one Diné educator and artist who transformed her business’ social media site into a powerful platform to educate people about the violence against Palestinians. After examining the rhetorical strategies that underlie this example of Diné civics and solidarity, we discuss how the legacy of Indigenous civics and solidarity with/for Palestine can contribute to teaching solidarities and activism for a free Palestine.